Urban geography : a critical introduction - Jonas, Andrew E. G., 1961-; McCann, Eugene; Thomas, Mary E. (Mary Elizabeth), 1970- (Chichester, West Sussex, UK ; Malden, MA, USA : John Wiley & Sons, Ltd, 2015)
"Urban Geography a comprehensive introduction to a variety of issues relating to contemporary urban geography, including patterns and processes of urbanization, urban development, urban planning, and life experiences in modern cities. Reveals both the diversity of ordinary urban geographies and the networks, flows and relations which increasingly connect cities and urban spaces at the global scale Uses the city as a lens for proposing and developing critical concepts which show how wider social processes, relations, and power structures are changing Considers the experiences, lives, practices, struggles, and words of ordinary urban residents and marginalized social groups rather than exclusively those of urban elites Shows readers how to develop critical perspectives on dominant neoliberal representations of the city and explore the great diversity of urban worlds "--
"Reveals both the diversity of ordinary urban geographies and the networks, flows and relations which increasingly connect cities and urban spaces at the global scale"--
Includes bibliographical references and index.
Keywords: Urban geography; Human geography